Crafting luxury : craftsmanship, manufacture, technology and the retail environment /: craftsmanship, manufacture, technology and the retail environment. (2022) - Borstrock, Shaun; Manlow, Veronica; Bloomfield, Mark; Carta, Silvio
No abstract available